FABRIKASI MATERIALAISI 4140 UNTUK PEMBUATAN BUSHING PADA DRAGBAR MESIN CRUSHER - Masbin Dahlan; Ilmawan Suryapradana (Unit Penelitian, dan Pengabdian Masyarakat (UPPM) Politeknik ATI Makassar, 2023)
AISI 4140 material is low-alloy steel that is widely used in its applications, which can be seen in automotive axle components. Based on these applications, it can be seen that AISI 4140 material is widely used in components that require high durability and hardness. The use of AISI 4140 in the mining industry is as a sleeve for the crusher unit drawbar. The sleeve material must go through a production process in the form of turning until it reaches the required dimensions. Case components must be durable and strong (with a long life) so that they do not hinder the production process in a company such as a coal company. Planning and using equipment and choosing the right materials can minimize production costs and speed up processes. This method can save production costs because it can reduce the 800 bushels per year needed in the mining area. This study aims to determine the factors that affect the performance of the case to increase the work efficiency of the crushing unit and reduce downtime due to damage to the case.